ANALISIS PEMASARAN TEMPE PADA INDUSTRI RUMAH TANGGA â€œMULTI BAROKAHâ€ DI KOTA PALU - Nilawati, Iyut (AGROTEKBIS, 2015)
Marketing is all the activities related to the business of marketing products, including related marketing agencies path before it reached the hands of consumers, tempeh is almost always through intermediaries. Path traversed by the products of producers with or without intermediaries to reach the consumers known to form marketing channels. Tempe sold with a simple form of marketing channels, starting from middlemen, retailers up to end consumers. This study aims to determine the form of marketing channels tempe on Home Industry